Microcirculatory tissue oxygenation correlates with kidney function after transcatheter aortic valve implantation–Results from a prospective observational study - Dietrich, Maximilian; Antonovici, Ana; Hölle, Tobias; Nusshag, Christian; Kapp, Anne-Christine; Studier-Fischer, Alexander; Arif, Rawa; Nickel, Felix; Weigand, Markus Alexander; Frey, Norbert; Lichtenstern, Christoph; Leuschner, Florian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Kidney dysfunction is common in patients with aortic stenosis (AS) and correction of the aortic valve by transcatheter aortic valve replacement (TAVR) often affects kidney function. This may be due to microcirculatory changes. Methods: We evaluated skin microcirculation with a hyperspectral imaging (HSI) system (TIVITA® Tissue), and compared tissue oxygenation (StO2), near-infrared perfusion index (NIR), tissue hemoglobin index (THI) and tissue water index (TWI) in 40 patients undergoing TAVR versus 20 control patients. HSI parameters were measured before TAVR (t1), directly after TAVR (t2), and postinterventional day 3 (t3). The primary outcome was the correlation of tissue oxygenation (StO2) to the creatinine level after TAVR. Results: We performed 116 HSI image recordings in patients undergoing TAVR for the treatment of severe aortic stenosis and 20 HSI image recordings in control patients. Patients with AS had a lower THI at the palm (p=0.034) and a higher TWI at the fingertips (p=0.003) in comparison to control patients. TAVR led to an increase of TWI, but had no uniform enduring effect on StO2 and THI. Tissue oxygenation StO2 at both measurement sites correlated negatively with creatinine levels after TAVR at t2 (palm: ρ=-0.415; p=0.009; fingertip: ρ=-0.519; p<0.001) and t3 (palm: ρ=-0.427; p=0.008; fingertip: ρ=-0.398; p=0.013). Patients with higher THI at t3 reported higher physical capacity and general health scores 120 days after TAVR. Conclusion: HSI is a promising technique for periinterventional monitoring of tissue oxygenation and microcirculatory perfusion quality, which are related to kidney function, physical capacity and clinical outcomes after TAVR.